A corrosion-resistant carbon carrier for hydrogen fuel cells and a preparation method thereof

By doping and recombining graphene with carbon black, the problem of insufficient activity and durability of platinum carbon catalysts in hydrogen fuel cells is solved, and higher catalyst activity and corrosion resistance are achieved, extending the service life of the fuel cell.

CN115763836BActive Publication Date: 2025-03-07INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211396045.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-08
Publication Date
2025-03-07
Estimated Expiration
2042-11-08

AI Technical Summary

Technical Problem

The activity and durability of the platinum carbon catalyst used in existing hydrogen fuel cells is insufficient, especially during the start-stop process of fuel cells, the carbon support is prone to corrosion, resulting in a decrease in catalyst activity and short service life.

Method used

By doping and passivating the graphene, the interaction force between it and the carbon black is enhanced, and the preparation of composite support is uniformly dispersed, the surface defects of the graphene are repaired, and its corrosion resistance is improved.

Benefits of technology

It significantly improves the activity and durability of the platinum carbon catalyst, reduces the corrosion current density of the carbon carrier, and extends the service life of the hydrogen fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115763836B_ABST
    Figure CN115763836B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of fuel cells, and specifically relates to a corrosion-resistant carbon carrier for hydrogen fuel cells and a preparation method thereof. In order to improve the activity and corrosion resistance of platinum-carbon catalysts, the present invention first modifies graphene, and enhances the interaction between graphene and carbon black by doping halogen ions; by passivating graphene, the stability of graphene surface functional groups is improved, and the corrosion resistance of graphene is enhanced. Secondly, with the aid of auxiliary agents, the carbon black is evenly dispersed and anchored on the graphene, and the two-dimensional layered structure of graphene is fully utilized while repairing the surface defects of graphene, thereby increasing the mass transfer effect of the carbon carrier. Finally, the graphene is compounded with carbon black to overcome graphene agglomeration and increase its tap density; high-temperature pickling and water washing are performed to further remove harmful metal ions remaining in the preparation process and improve the corrosion resistance of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a corrosion-resistant carbon carrier for hydrogen fuel cells and a preparation method thereof. Background Art

[0002] Hydrogen fuel cells are a new energy battery with zero emissions and no pollution. They convert the chemical energy of hydrogen and oxygen into electrical energy through catalysts and are the best choice for the new generation of passenger car batteries. At present, the bottleneck problem restricting the large-scale commercial application of fuel cells is the insufficient activity and durability of the platinum-carbon catalyst used. Among them, the carbon carrier, as an important component of the catalyst, directly affects the electrocatalytic performance of the platinum-carbon catalyst. The good interaction between the carbon carrier and the platinum particles can not only improve the activity of the catalyst and reduce the cost, but also enhance the stability of the catalyst. However, during the start-stop process of the fuel cell, some oxygen will leak to the anode, resulting in an increase in voltage and severe corrosion of the carbon carrier, thereby reducing the activity of the platinum-carbon catalyst and greatly reducing the service life of the hydrogen fuel cell.

[0003] According to literature reports, the corrosion resistance of carbon carriers increases with the increase of graphitization degree. When the temperature is >1600℃, the corrosion resistance of carbon carriers is significantly improved. Among them, Wang Zhengluo (patent number: CN113506885A) prepared graphitized carbon carriers by low-temperature catalytic graphitization; using transition metal ions as catalysts, the graphitization temperature of carbon materials was reduced from more than 1600℃ to less than 1000℃, saving energy consumption while obtaining graphitized carbon carriers. However, as the degree of graphitization increases, the number of surface functional groups and defects will be significantly reduced, resulting in the problem that platinum metal particles are difficult to load and have low activity.

[0004] Compared with traditional carbon black, graphene not only has a larger specific surface area (theoretical specific surface area is up to 2620m 2 / g), which can provide a large number of active sites for metal loading; and graphene has excellent chemical stability, good conductivity, and is easy to be surface modified, making it an ideal carbon carrier. However, due to the existence of van der Waals forces, it is very easy to agglomerate during the drying process. The agglomerated graphene not only has a greatly reduced specific surface area, but is also extremely difficult to disperse, limiting its application. To solve the agglomeration problem, most researchers add nanomaterials as insulators. On the one hand, the introduction of nanomaterials can establish a three-dimensional network structure, improve the longitudinal conductivity of graphene, and avoid graphene stacking; on the other hand, through carbon-carbon composites, graphene surface defects can be repaired and the corrosion resistance of graphene can be improved. Among them, the researchers prepared a three-dimensional network structure of graphene / carbon nanotubes by filtration, which effectively inhibited the agglomeration of graphene and significantly improved the longitudinal conductivity of graphene. (Composites Part A: Applied Science and Manufacturing, 2020, 129: 105712.) However, due to the dense layered structure of graphene, the filtration efficiency is low, and carbon nanotubes are expensive and are not suitable for practical applications. Carbon black is cheap and has a mesoporous structure suitable for three-phase interface transmission in fuel cells. It can be used as an insulator to improve the performance of graphene carbon carriers. Shao Zhigang (patent number: CN109935846A) prepared a carbon-based / graphene composite carrier by a simple and low-cost method to improve the activity and durability of fuel cell catalysts. The method is simple and easy to implement, but the graphene oxide used in the preparation process has many defects, and some harmful metal ions will remain during the preparation process, resulting in poor corrosion resistance of the material. Therefore, there is an urgent need to explore a carbon-carbon composite material with strong carbon-carbon interaction, high chemical stability, and low harmful metal ion content to improve the activity and corrosion resistance of platinum carbon catalysts. Summary of the invention

[0005] The present invention aims at the problems existing in the prior art. Firstly, the graphene is modified and passivated by doping to enhance the interaction between graphene and carbon black. By passivating the graphene, the stability of the functional groups on the surface of the graphene is improved, and the corrosion resistance of the graphene is enhanced. Secondly, with the aid of an auxiliary agent, the carbon black is evenly dispersed and anchored on the graphene, and the two-dimensional layered structure of the graphene is fully utilized while repairing the surface defects of the graphene, thereby increasing the mass transfer effect of the carbon carrier. Finally, the graphene is compounded with the carbon black to overcome the agglomeration of the graphene and increase its tap density. High-temperature pickling and water washing are performed to further remove the harmful metal ions remaining in the preparation process and improve the corrosion resistance of the composite material.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for preparing a corrosion-resistant carbon carrier for a hydrogen fuel cell comprises the following steps:

[0008] Step 1, mixing graphene and a dopant by ultrasonic stirring, and then vacuum impregnating, drying at 60-100° C. for 12-24 hours after impregnation, heating the mixture to 800-1200° C. at a heating rate of 1-5° C. / min under argon purge, keeping the temperature constant for 2-6 hours, and cooling to room temperature to obtain doped graphene;

[0009] Step 2, under argon purge, heating the doped graphene to 1000° C. at a heating rate of 2° C. / min, keeping the temperature constant for 2 to 6 hours, performing a passivation treatment, and cooling to room temperature to obtain passivated graphene;

[0010] Step 3, mixing the passivated graphene, carbon black, dispersant, additive and water by ultrasonic stirring, then magnetic stirring, and filtering to obtain a composite carrier;

[0011] Step 4, wetting the composite carrier with anhydrous ethanol, and then completely wetting the composite carrier with an acid wash agent;

[0012] Step 5, heating the composite carrier obtained in step 4 in a water bath, and then washing it by ultrasonic filtration with hot water, the filtered solution is neutral, and drying is performed to obtain a purified carbon-carbon composite carrier;

[0013] Step 6, under argon purge, heating the purified carbon-carbon composite carbon carrier to 800-1600° C. at a heating rate of 2° C. / min, keeping the temperature constant for 2-6 hours, and cooling to room temperature to obtain a corrosion-resistant carbon carrier.

[0014] Furthermore, in step 1, the graphene is graphene oxide reduced at 600° C., the dopant is a mixture of one or two of melamine, phosphoric acid, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate in any ratio, and the mass ratio of graphene to dopant is 1:1 to 5.

[0015] Furthermore, in step 1, the mixture is stirred and mixed for 3 hours, and vacuum impregnated for 6 to 12 hours.

[0016] Furthermore, in step 3, the carbon black is a mixture of one or two of XC-72, XC-72R, KB-300, KB-600J, and acetylene black in any ratio, the dispersant is ethylene glycol, isopropanol, ethanol or propylene glycol, the auxiliary agent is a mixture of one or two of sodium polyacrylate, acrylic resin, ethylenediamine, sodium citrate, pyrrole, and pyridine in any ratio, the mass ratio of passivated graphene, carbon black, auxiliary agent and water is 3:1:1:100 to 1:3:9:500, and the volume ratio of dispersant to water is 1:1 to 4.

[0017] Furthermore, in step 3, the mixture is stirred with ultrasonic stirring for 1 hour and stirred with magnetic stirring for 4 to 12 hours.

[0018] Furthermore, the pickling agent in step 4 is dilute hydrochloric acid, concentrated hydrochloric acid, hydrofluoric acid, sulfuric acid or nitric acid.

[0019] Furthermore, in step 5, the water bath heating temperature is 60°C, the time is 0.5 to 6 hours, and the temperature of the hot water is 75 to 100°C.

[0020] Furthermore, the argon purging time in step 1, step 2 and step 6 is 20 minutes.

[0021] A corrosion-resistant carbon carrier for hydrogen fuel cells, with an iron ion content of 19.75 to 43.31 ppm and a corrosion current density of 20.4 to 101.9 μA / cm at 1.5 V 2 .

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] The preparation method of the graphene / carbon black composite carrier for hydrogen fuel cells of the present invention changes the functional group configuration of the graphene surface by doping and passivating the graphene, improves the interaction between the graphene and the carbon black, and enhances the stability of the graphene; by compounding the graphene and the carbon black, on the one hand, partial defects on the graphene surface are repaired, and the addition of carbon black can inhibit the agglomeration of the graphene, thereby promoting each other; by adding an auxiliary agent during the compounding process, the carbon black can be more evenly dispersed on the graphene flakes, further reducing the agglomeration of the graphene and increasing the corrosion resistance of the carrier. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope photo of the corrosion-resistant carbon carrier of the present invention. From the photo, it can be seen that the carbon black is evenly distributed in the middle of the graphene sheet, forming a stable three-dimensional network structure, which effectively inhibits the agglomeration of graphene;

[0025] Figure 2 : is a nitrogen adsorption-desorption curve diagram of the corrosion-resistant carbon support of the present invention, which is a typical IV type adsorption-desorption curve, indicating that there are mesopores and macropores stacking;

[0026] Figure 3 This is the pore size distribution diagram of the corrosion-resistant carbon carrier of the present invention. It can be seen that the corrosion-resistant carbon carrier of the present invention is mainly mesopores, and the pore size is concentrated in 2-100nm, which is conducive to the formation of a three-phase interface in the catalytic process of the fuel cell and improves the electrocatalytic performance of the catalyst;

[0027] Figure 4 This is a comparison chart of the corrosion current density of the corrosion-resistant carbon carrier of the present invention and ordinary carbon black at 1.5V. It can be seen that the corrosion current density of the corrosion-resistant carbon carrier of the present invention is much lower than that of ordinary carbon black, indicating that the composite material has high chemical stability and high corrosion resistance. DETAILED DESCRIPTION

[0028] Example 1

[0029] A method for preparing a corrosion-resistant carbon carrier for a hydrogen fuel cell comprises the following steps:

[0030] (1) taking 1 g of 600° C. reduced graphene oxide and 1 g of melamine, mixing them by ultrasonic stirring for 3 hours, and then vacuum impregnating them for 12 hours to fully mix the graphene and melamine. After the impregnation, the mixture was dried in a 60° C. forced air drying oven for 12 hours, and then placed in a horizontal tube furnace, purged with argon for 20 minutes, and heated to 800° C. at a heating rate of 2° C. / min, and kept at this temperature for 2 hours to obtain doped graphene;

[0031] (2) placing the doped graphene in a tube furnace, purging with argon for 20 minutes, heating to 1000° C. at a heating rate of 2° C. / min, and keeping the temperature constant for 2 hours for passivation treatment to obtain passivated graphene;

[0032] (3) 0.3 g of passivated graphene, 0.3 g of carbon black XC-72, 0.6 g of carbon black XC-72R, 80 mL of dispersant ethylene glycol, 0.9 g of auxiliary agent sodium polyacrylate and 320 mL of water were mixed by ultrasonic stirring for 1 hour, magnetically stirred in a water bath at 80 ° C for 4 hours, and filtered to obtain a composite carrier;

[0033] (4) Place the composite carrier in a glass cup, add 2 mL of anhydrous ethanol to moisten it, then slowly add 500 mL of concentrated hydrochloric acid and stir evenly with a glass rod;

[0034] (5) placing the beaker in a 60°C water bath and heating for 0.5 hours, taking out the beaker, letting it stand, pouring off the supernatant, filtering, and then ultrasonically filtering and washing with 75°C hot water for 3 times, and drying to obtain a corrosion-resistant carbon-carbon composite carrier;

[0035] (6) The purified carbon-carbon composite carbon carrier was placed in a tubular furnace, purged with argon for 20 minutes, and then heated to 800°C and kept at this temperature for 2 hours; the heating rate was 2°C / min; after cooling to room temperature, a corrosion-resistant carbon carrier was obtained; the iron content of the corrosion-resistant carbon carrier was 36.46 ppm, and the corrosion current density at 1.5 V was 101.9 μA / cm 2 .

[0036] Example 2

[0037] A method for preparing a corrosion-resistant carbon carrier for a hydrogen fuel cell comprises the following steps:

[0038] (1) taking 1 g of 600°C reduced graphene oxide and 5 g of phosphoric acid, mixing them by ultrasonic stirring for 3 hours, and then vacuum impregnating them for 6 hours to fully mix the graphene and the phosphoric acid. After the impregnation, drying them in a 100°C forced air drying oven for 24 hours, and then placing the mixture in a horizontal tube furnace, purging with argon for 20 minutes, heating them to 1200°C at a heating rate of 2°C / min, and keeping the temperature constant for 6 hours to obtain doped graphene;

[0039] (2) placing the doped graphene in a tube furnace, purging with argon for 20 minutes, heating to 1000°C at a heating rate of 2°C / min, and keeping the temperature constant for 6 hours for passivation treatment to obtain passivated graphene

[0040] (3) 0.9 g of passivated graphene, 0.3 g of carbon black KB-300, 200 mL of dispersant isopropanol, 0.6 g of auxiliary acrylic resin, 0.3 g of sodium citrate and 200 mL of water were mixed by ultrasonic stirring for 1 hour, magnetic stirring in a water bath at 80° C. for 12 hours, and the composite carrier was obtained by filtration;

[0041] (4) Place the composite carrier in a glass cup, add 1 mL of anhydrous ethanol to moisten it, then slowly add 500 mL of dilute hydrochloric acid or concentrated hydrochloric acid and stir evenly with a glass rod;

[0042] (5) placing the beaker in a 60°C water bath and heating for 6 h, taking out the beaker, letting it stand, pouring off the supernatant, filtering, and then ultrasonically filtering and washing with 100°C hot water for 10 times, and drying to obtain a corrosion-resistant carbon-carbon composite carrier;

[0043] (6) The purified carbon-carbon composite carbon carrier was placed in a tubular furnace, purged with argon for 20 minutes, and then heated to 1600°C and kept at this temperature for 6 hours; the heating rate was 2°C / min; after cooling to room temperature, a corrosion-resistant carbon carrier was obtained; the iron content of the corrosion-resistant carbon carrier was 19.75 ppm, and the corrosion current density at 1.5 V was 20.4 μA / cm 2 .

[0044] Example 3

[0045] A method for preparing a corrosion-resistant carbon carrier for a hydrogen fuel cell comprises the following steps:

[0046] (1) 1 g of 600°C reduced graphene oxide, 1 g of diammonium hydrogen phosphate, and 1 g of ammonium dihydrogen phosphate were mixed by ultrasonic stirring for 3 hours, and then vacuum impregnated for 10 hours to fully mix the graphene with diammonium hydrogen phosphate and ammonium dihydrogen phosphate. After the impregnation, the mixture was dried in a blast drying oven at 80°C for 18 hours, and then placed in a horizontal tube furnace, purged with argon for 20 minutes, and heated to 1000°C at a heating rate of 2°C / min, and kept at this temperature for 4 hours to obtain doped graphene;

[0047] (2) placing the doped graphene in a tube furnace, purging with argon for 20 minutes, heating to 1000°C at a heating rate of 2°C / min, and keeping the temperature constant for 4 hours for passivation treatment to obtain passivated graphene

[0048] (3) 1 g of passivated graphene, 1 g of carbon black KB-600J, 100 mL of dispersant ethanol, 2 g of auxiliary agent ethylenediamine and 300 mL of water were mixed by ultrasonic stirring for 1 hour, then magnetic stirring for 8 hours, and filtered to obtain a composite carrier;

[0049] (4) Place the composite support in a plastic beaker, add 2 mL of anhydrous ethanol to moisten it, then slowly add 500 mL of hydrofluoric acid and stir evenly with a glass rod;

[0050] (5) placing the beaker in a 60°C water bath and heating for 3 h, taking out the beaker, letting it stand, pouring off the supernatant, filtering, and then ultrasonically filtering and washing with 90°C hot water for 6 times, and drying to obtain a corrosion-resistant carbon-carbon composite carrier;

[0051] (6) The purified carbon-carbon composite carbon carrier was placed in a tubular furnace, purged with argon for 20 minutes, and then heated to 1200°C and kept at this temperature for 4 hours; the heating rate was 2°C / min; after cooling to room temperature, a corrosion-resistant carbon carrier was obtained; the iron content of the corrosion-resistant carbon carrier was 34.90 ppm, and the corrosion current density at 1.5 V was 38.2 μA / cm 2 .

[0052] Example 4

[0053] A method for preparing a corrosion-resistant carbon carrier for a hydrogen fuel cell comprises the following steps:

[0054] (1) taking 1 g of 600°C reduced graphene oxide and 4 g of melamine, mixing them by ultrasonic stirring for 3 hours, and then vacuum impregnating them for 9 hours to fully mix the graphene and melamine. After the impregnation, drying them in a 60°C forced air drying oven for 14 hours, and then placing the mixture in a horizontal tube furnace, purging with argon for 20 minutes, heating them to 900°C at a heating rate of 2°C / min, and keeping the temperature constant for 2 hours to obtain doped graphene;

[0055] (2) placing the doped graphene in a tube furnace, purging with argon for 20 minutes, heating to 1000°C at a heating rate of 2°C / min, and keeping the temperature constant for 2 hours for passivation treatment to obtain passivated graphene

[0056] (3) 0.5 g of passivated graphene, 0.5 g of carbon black XC-72, 0.5 g of KB-300, 200 mL of dispersant propylene glycol, 2 g of auxiliary agent pyrrole and 200 mL of water were mixed by ultrasonic stirring for 1 hour, then magnetic stirring for 6 hours, and filtered to obtain a composite carrier;

[0057] (4) Place the composite carrier in a glass cup, add 1-2 mL of anhydrous ethanol to moisten it, then slowly add 500 mL of sulfuric acid and stir evenly with a glass rod;

[0058] (5) placing the beaker in a 60°C water bath and heating for 4 h, taking out the beaker, letting it stand, pouring off the supernatant, filtering, and then ultrasonically filtering and washing with 100°C hot water for 10 times, the filtered solution is neutral, and drying is performed to obtain a corrosion-resistant carbon-carbon composite carrier;

[0059] (6) The purified carbon-carbon composite carbon carrier was placed in a tubular furnace, purged with argon for 20 minutes, and then heated to 800°C and kept at this temperature for 4 hours; the heating rate was 2°C / min; after cooling to room temperature, a corrosion-resistant carbon carrier was obtained; the iron content of the corrosion-resistant carbon carrier was 37.25 ppm, and the corrosion current density at 1.5 V was 61.1 μA / cm 2 .

[0060] Example 5

[0061] A method for preparing a corrosion-resistant carbon carrier for a hydrogen fuel cell comprises the following steps:

[0062] (1) taking 1 g of 600° C. reduced graphene oxide and 3 g of diammonium hydrogen phosphate, mixing them under ultrasonic stirring for 3 hours, and then vacuum impregnating them for 10 hours to fully mix the graphene and diammonium hydrogen phosphate. After the impregnation, drying them in a blast drying oven at 80° C. for 18 hours, and then placing the mixture in a horizontal tube furnace, purging with argon for 20 minutes, heating them to 1000° C. at a heating rate of 2° C. / min, and keeping the temperature constant for 4 hours to obtain doped graphene;

[0063] (2) placing the doped graphene in a tube furnace, purging with argon for 20 minutes, heating to 1000°C at a heating rate of 2°C / min, and keeping the temperature constant for 4 hours for passivation treatment to obtain passivated graphene

[0064] (3) 0.5 g of passivated graphene, 1 g of carbon black acetylene black, 200 mL of dispersant ethylene glycol, 2 g of auxiliary agent pyridine and 200 mL of water were mixed by ultrasonic stirring for 1 hour, then magnetic stirring for 8 hours, and filtered to obtain a composite carrier;

[0065] (4) Place the composite support in a glass cup, add 2 mL of anhydrous ethanol to moisten it, then slowly add 500 mL of nitric acid and stir evenly with a glass rod;

[0066] (5) placing the beaker in a 60°C water bath and heating for 2 h, taking out the beaker, letting it stand, pouring off the supernatant, filtering, and then ultrasonically filtering and washing with 80°C hot water for 5 times, and drying to obtain a corrosion-resistant carbon-carbon composite carrier;

[0067] (6) The purified carbon-carbon composite carbon carrier was placed in a tubular furnace, purged with argon for 20 minutes, and then heated to 1300°C and kept at this temperature for 5 hours; the heating rate was 2°C / min; after cooling to room temperature, a corrosion-resistant carbon carrier was obtained; the iron content of the corrosion-resistant carbon carrier was 43.31 ppm, and the corrosion current density at 1.5 V was 50.9 μA / cm 2 .

[0068] Example 6

[0069] A method for preparing a corrosion-resistant carbon carrier for a hydrogen fuel cell comprises the following steps:

[0070] (1) 1 g of 600° C. reduced graphene oxide and 4 g of melamine were mixed by ultrasonic stirring for 3 hours, and then vacuum impregnated for 9 hours to fully mix the graphene and melamine. After the impregnation, the mixture was dried in a 100° C. forced air drying oven for 20 hours. The mixture was then placed in a horizontal tube furnace, purged with argon for 20 minutes, and heated to 1200° C. at a heating rate of 2° C. / min, and kept at this temperature for 6 hours to obtain doped graphene;

[0071] (2) placing the doped graphene in a tube furnace, purging with argon for 20 minutes, heating to 1000° C. at a heating rate of 2° C. / min, and maintaining the temperature for 6 hours for passivation treatment to obtain passivated graphene;

[0072] (3) 1 g of passivated graphene, 0.5 g of carbon black KB-300, 200 mL of dispersant ethylene glycol, 1 g of auxiliary agent pyridine and 200 mL of water were mixed by ultrasonic stirring for 1 hour, then magnetic stirring for 12 hours, and filtered to obtain a composite carrier;

[0073] (4) Place the composite support in a glass cup, add 2 mL of anhydrous ethanol to moisten it, then slowly add 500 mL of sulfuric acid and stir evenly with a glass rod;

[0074] (5) placing the beaker in a 60°C water bath and heating for 0.5 h, taking out the beaker, letting it stand, pouring off the supernatant, filtering, and then ultrasonically filtering and washing with 100°C hot water for 7 times, and drying to obtain a corrosion-resistant carbon-carbon composite carrier;

[0075] (6) The purified carbon-carbon composite carbon carrier was placed in a tubular furnace, purged with argon for 20 minutes, and then heated to 1600°C and kept at this temperature for 2 hours; the heating rate was 2°C / min; after cooling to room temperature, a corrosion-resistant carbon carrier was obtained; the iron content of the corrosion-resistant carbon carrier was 26.85 ppm, and the corrosion current density at 1.5 V was 56.1 μA / cm 2 .

[0076] The corrosion current density and Fe 3+ The content comparison is shown in Table 1:

[0077] Table 1 Corrosion current density and Fe 3+ Content comparison table

[0078]

Claims

1. A method for preparing a corrosion-resistant carbon carrier for a hydrogen fuel cell, characterized in that: The following steps are involved: Step 1, mixing graphene and a dopant by ultrasonic stirring, and then vacuum impregnating, drying at 60-100° C. for 12-24 hours after impregnation, heating the mixture to 800-1200° C. at a heating rate of 1-5° C. / min under argon purge, keeping the temperature constant for 2-6 hours, and cooling to room temperature to obtain doped graphene, wherein the dopant is a mixture of one or two of melamine, phosphoric acid, diammonium hydrogen phosphate, and diammonium dihydrogen phosphate in any ratio; Step 2, under argon purge, heating the doped graphene to 1000° C. at a heating rate of 2° C. / min, keeping the temperature constant for 2 to 6 hours, performing a passivation treatment, and cooling to room temperature to obtain passivated graphene; Step 3, mixing the passivated graphene, carbon black, dispersant, additive and water by ultrasonic stirring, then magnetic stirring, and filtering to obtain a composite carrier; Step 4, wetting the composite carrier with anhydrous ethanol, and then completely wetting the composite carrier with an acid wash agent; Step 5, heating the composite carrier obtained in step 4 in a water bath, and then washing it by ultrasonic filtration with hot water, the filtered solution is neutral, and drying is performed to obtain a purified carbon-carbon composite carrier; Step 6, under argon purge, heating the purified carbon-carbon composite carbon carrier to 800-1600° C. at a heating rate of 2° C. / min, keeping the temperature constant for 2-6 hours, and cooling to room temperature to obtain a corrosion-resistant carbon carrier.

2. The method for preparing a corrosion-resistant carbon support for a hydrogen fuel cell according to claim 1, characterized in that: In the step 1, the graphene is graphene oxide reduced at 600° C., and the mass ratio of graphene to dopant is 1:1-5.

3. The method for preparing a corrosion-resistant carbon support for a hydrogen fuel cell according to claim 1, characterized in that: In the step 1, the mixture is stirred for 3 hours and vacuum impregnated for 6 to 12 hours.

4. The method for preparing a corrosion-resistant carbon support for a hydrogen fuel cell according to claim 1, characterized in that: In the step 3, the carbon black is a mixture of one or two of XC-72, XC-72R, KB-300, KB-600J, and acetylene black in any ratio, the dispersant is ethylene glycol, isopropanol, ethanol or propylene glycol, the auxiliary agent is a mixture of one or two of sodium polyacrylate, acrylic resin, ethylenediamine, sodium citrate, pyrrole, and pyridine in any ratio, the mass ratio of passivated graphene, carbon black, auxiliary agent and water is 3:1:1:100 to 1:3:9:500, and the volume ratio of dispersant to water is 1:1 to 4.

5. The method for preparing a corrosion-resistant carbon support for a hydrogen fuel cell according to claim 1, characterized in that: In step 3, the mixing is carried out by ultrasonic stirring for 1 hour and by magnetic stirring for 4 to 12 hours.

6. The method for preparing a corrosion-resistant carbon carrier for a hydrogen fuel cell according to claim 1, characterized in that: The pickling agent in step 4 is dilute hydrochloric acid, concentrated hydrochloric acid, hydrofluoric acid, sulfuric acid or nitric acid.

7. The method for preparing a corrosion-resistant carbon carrier for a hydrogen fuel cell according to claim 1, characterized in that: In step 5, the water bath heating temperature is 60° C., the time is 0.5 to 6 hours, and the temperature of the hot water is 75 to 100° C.

8. The method for preparing a corrosion-resistant carbon support for a hydrogen fuel cell according to claim 1, characterized in that: The argon purging time in step 1, step 2 and step 6 is 20 minutes.

9. A corrosion-resistant carbon support for a hydrogen fuel cell prepared according to the preparation method according to any one of claims 1 to 8, characterized in that: The corrosion current density of the carbon support at 1.5V is 20.4-101.9 μA / cm 2 , the iron ion content is 19.75~43.31ppm.

Citation Information

Patent Citations

  • Fuel cell electrocatalyst carrier and preparation method thereof

    CN109935846A

  • Graphitized carbon carrier for hydrogen fuel cell, preparation method of graphitized carbon carrier and cell catalyst of graphitized carbon carrier

    CN113506885A

  • Preparation method of heteroatom doped graphene hierarchical pore carbon material

    CN106044754A

  • Carbon support for fuel cell catalyst and preparation method thereof

    US20170005342A1